2016
DOI: 10.1016/j.aogh.2016.04.335
|View full text |Cite
|
Sign up to set email alerts
|

Increasing HCT uptake among pregnant women in Nigeria; Evaluating the TBA and PHC Integration (TAPI) Model intervention in Ebonyi State, Nigeria

Abstract: development meetings were held with university faculty, UMB, and CCCRN. The training capacity of facility and faculty were developed based on a needs assessment. UNN faculty and UMB/ CCCRN faculty taught the course jointly. Evaluation methods including pre/post tests, OSCE's, evaluation forms, and logbooks were jointly developed. Course alumni were followed up at 6 and 18 months using online surveys and telephone interviews to assess how useful the course was to them at their current workplaces. Outcome and Ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Highlights of the success stories include: TBAs ability to apply for training and experience in universal precautions and safe birth practices to the potential of reducing maternal sepsis and infection transmission [12]; TBAs are able to offer health education to their clients on issues around HIV and PMTCT [13-15] while offering risk assessment; Dissemination of HIV education/information in home based and community approach [13,14]; Ability to offer HCT to their clients [10]; Able to refer HIV positive women to health centres [12]. Provision of alternative, low-cost, efficacious communitybased interventions outside health facilities for more women living in remote areas to access HIV care, treatment and support as well as other health care needs [7]; Several studies have thus concluded that Traditional birth attendants have a role in the prevention of mother to child transmission of HIV [10,[12][13][14][15].…”
Section: Success Stories Of Tba Involvement In Pmtct; Efforts To Bridge the Gaps In Pmtctmentioning
confidence: 99%
See 1 more Smart Citation
“…Highlights of the success stories include: TBAs ability to apply for training and experience in universal precautions and safe birth practices to the potential of reducing maternal sepsis and infection transmission [12]; TBAs are able to offer health education to their clients on issues around HIV and PMTCT [13-15] while offering risk assessment; Dissemination of HIV education/information in home based and community approach [13,14]; Ability to offer HCT to their clients [10]; Able to refer HIV positive women to health centres [12]. Provision of alternative, low-cost, efficacious communitybased interventions outside health facilities for more women living in remote areas to access HIV care, treatment and support as well as other health care needs [7]; Several studies have thus concluded that Traditional birth attendants have a role in the prevention of mother to child transmission of HIV [10,[12][13][14][15].…”
Section: Success Stories Of Tba Involvement In Pmtct; Efforts To Bridge the Gaps In Pmtctmentioning
confidence: 99%
“…While trained TBAs are not considered skilled birth attendants (SBAs), their potential contribution has been recognized in diagnosing labour, ensuring clean deliveries, detecting and referring maternal complications, providing hygienic cord-care, supporting early exclusive breastfeeding, administration of post exposure prophylaxis(PEP), immunizations, nutritional advice, and providing counselling on a number of health topics including HIV and PMTCT [10,[12][13][14][15]. Though with these beneficial contributions by TBA in involvement in MCH and PMTCT programs, the role of TBAs in improving maternal health has been heavily debated, especially in the context of a renewed focus on Millennium Development Goals (MDGs).…”
Section: Challenges Of Tba Involvement In Pmtctmentioning
confidence: 99%